Determinants of arterial health in adolescence and young adulthood - Holma, Juulia (My University, 2022)
Atherosclerotic disease process begins already in childhood although consequences such as myocardial infarction and ischemic stroke usually appear in adulthood or old age. Cardiovascular risk factors were first recognized in adults with atherosclerosis, and studies were extended to examine whether these risk factors are present already in children and associated with the early phases of the disease process. The primary aim of this work is to study the associations of the most important cardiovascular risk and protective factors in childhood and adolescence and arterial health in young adulthood. Secondary aim is to study how these risk factors are altered by a 20-year dietary intervention. Intima media thickness (IMT) is a measurement of the arterial wall and is a preclinical marker of atherosclerosis. It is commonly used in cardiovascular studies, since it can be measured non-invasively in ultrasound studies. IMT correlates with risk factors and is related to atherosclerotic lesions. In this study aortic and carotid IMT were measured at ages 11, 13, 15, 17 and 19 years, and the association of risk and protective factors with IMT are examined both in cross-sectional and longitudinal settings. This work is a part of The Special Turku Coronary Risk Factor Intervention Project (STRIP). This study shows that BMI, waist and hip circumferences, and systolic blood pressure associate with thicker arterial IMT cross-sectionally at every age-point and longitudinally from adolescence to young adulthood. Children receiving dietary intervention had healthier diet, lower total cholesterol, low-density lipoprotein cholesterol, apolipoprotein B and serum insulin values than children in the control group. These results provide important knowledge for prevention of cardiovascular disease and highlight the importance of maintaining normal weight and blood pressure already at early age in order to prevent atherosclerosis in adulthood.

Ateroskleroosin tautiprosessin tiedetään alkavan jo lapsuudessa, vaikka sen seuraukset, kuten sydäninfarkti ja aivoinfarkti useimmiten nähdään vasta aikuisuudessa. Alun perin ateroskleroosiin yhteydessä olevia kardiovaskulaarisia riskitekijöitä tunnistettiin aikuisilla, joiden tiedettiin sairastavan ateroskleroosia. Tämän jälkeen tutkimuksia laajennettiin lapsiin, jotta voitiin tutkia, esiintyykö samoja riskitekijöitä myös lapsilla ja ovatko riskitekijät näin ollen yhteydessä ateroskleroosin myös jo sen varhaisemmissa vaiheissa. Tämän tutkimuksen tavoitteena oli tutkia tärkeimpien lapsuuden- ja nuoruudenaikaisten kardiovaskulaaristen riski- ja suojatekijöiden yhteyttä varhaiseen ateroskleroosiin. Toissijaisena tavoitteena oli tutkia, miten interventioruokavalio vaikuttaa näiden riski- ja suojatekijöiden esiintymiseen. Intima-media paksuus (intima-media thickness, IMT) kertoo valtimon seinämän paksuudesta ja on ateroskleroosin prekliininen markkeri. Se on yleisesti käytetty kardiovaskulaarisissa tutkimuksissa, sillä sitä voidaan mitata melko helposti, ei-invasiivisesti ultraäänitutkimuksella. IMT korreloi riskitekijöihin ja on yhteydessä ateroskleroottisiin leesioihin. Paksumpi IMT on yhteydessä myös korkeampaan sydän- ja aivoinfarktiriskiin. Tässä työssä aortan ja kaulavaltimon IMT on mitattu 11, 13, 15, 17 ja 19 vuoden iässä, ja riski- ja suojatekijöiden yhteyttä IMT:n paksuuteen on tutkittu sekä poikittais- että pitkittäistutkimuksilla. Tämä työ on toteutettu osana Sepelvaltimotaudin Riskitekijöiden Interventioprojektia (STRIP). Tämä tutkimus osoittaa, että BMI, vyötärön- ja lantionympärys sekä systolinen verenpaine ovat yhteydessä verisuonien paksumpaan IMT:hen jokaisessa tutkitussa ikäpisteessä sekä nuoruusiästä varhaiseen aikuisuuteen. Lapsilla, jotka saivat ruokavalioneuvontaa, oli terveellisempi ruokavalio, matalampi kokonaiskolesteroli, LDL-kolesteroli sekä matalampi apolipoproteiini B ja seerumin insuliinitaso kuin kontrolliryhmän lapsilla. Kardiovaskulaarisairauksien lapsuuden- ja nuoruudenaikaisen kehityksen ehkäisyn kannalta on siis erityisen tärkeää pyrkiä ylläpitämään normaalipainoa ja optimaalista verenpainetta.
Keywords: Intima-media thickness, cardiovascular disease, childhood, risk factors